2015
DOI: 10.1002/jmri.24915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the treatment response to neoadjuvant chemotherapy in locally advanced breast cancer using combined magnetic resonance vascular maps and apparent diffusion coefficient

Abstract: The early changes of MR vascular maps and ADC are associated with the final treatment response of LABC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Also, the various chemotherapeutic drugs contribute differently to the variation in the primitive lesion, with significant consequences on imaging. Taxanes have been reported to have greater antiangiogenic activity compared to anthracyclines [ 29 ], and this antivascular effect, with the lack of surrounding inflammatory response, lowers the enhancement on tumor tissue, leading to underestimation of tumor size by MRI [ 5 ]. These effects were similar in our patients as the NAC protocol was the same, including both anthracyclines and taxanes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the various chemotherapeutic drugs contribute differently to the variation in the primitive lesion, with significant consequences on imaging. Taxanes have been reported to have greater antiangiogenic activity compared to anthracyclines [ 29 ], and this antivascular effect, with the lack of surrounding inflammatory response, lowers the enhancement on tumor tissue, leading to underestimation of tumor size by MRI [ 5 ]. These effects were similar in our patients as the NAC protocol was the same, including both anthracyclines and taxanes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a pCR is achieved in only 30% of the patients after the completion of NAC and thus determining factors and an accurate means to predict treatment response as early as possible are desirable for identifying patients who do not benefit from NAC (2). Several studies have demonstrated that dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is the most sensitive method for the assessment and prediction of treatment response to NAC (4)(5)(6)(7)(8). In addition, it has been demonstrated that multiparametric MRI (mpMRI) using morphological as well as additional functional parameters such as diffusion-weighted imaging (DWI) has the potential for improving the prediction of treatment response (6,(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer, MRI performed early in the course of neoadjuvant therapy (NAT) has proven capable of predicting the eventual tumor response before downstream changes in tumor size (11–13). The 2 MRI techniques that have been the most investigated for predicting therapeutic response to breast NAT are diffusion-weighted MRI (14) and dynamic contrast-enhanced MRI (15, 16), as well as their combination (17, 18). MT-MRI has not yet been investigated for evaluating (or predicting) response during therapy in locally advanced breast cancer.…”
Section: Introductionmentioning
confidence: 99%